THE VALIDATION OF THE TRANSFORMATION BETWEEN AN OLD GEODETIC REFERENCE FRAME AND A MODERN REFERENCE FRAME, BY USING EXTERNAL SPACE TECHNIQUES SITES: THE CASE STUDY OF THE HELLENIC GEODETIC REFERENCE SYSTEM OF 1987 - Doukas, Ioannis D.; Ampatzidis, Dimitrios; Kampouris, Vassileios (Boletim de Ciências Geodésicas, 2017)
Many of the old geodetic reference frames which realized in the previous decades using classical observations carry biases. These biases are mainly caused due to the problematic observations and/or the tectonic motion. That is the case of the official Greek geodetic reference frame which consists of classical and satellite observations. Herein, we present a rigorous approach of the reconstruction of the Greek official reference frame based on the modern geodetic reference frames and their ability to express the spatial position and the dynamic change of the stations. We applied the rigorous approach to ninety stations located in Greece and we compare it with the officially accepted procedure. We found a consistency at 59.4cm between the rigorous and the officially accepted approaches, respectively. The associated mean bias estimation was estimated at 51.4 cm, indicating the resistance of a rather large amount of systematic effects. In addition, the observed discrepancies between the two approaches show great inhomogeneity all over the country.